2009
DOI: 10.1111/j.1466-7657.2008.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

International perspectives on workplace bullying among nurses: a review

Abstract: Purpose: This article examines the nursing literature on workplace bullying with the aim of reaching a better understanding of the phenomenon. Background: Workplace bullying occurs in many occupations and workplaces, including nursing. Methods:The following databases were used for the literature review: CINAHL, PubMed, Pro Quest and EBSCO host. Only articles in English were used. Articles from outside the nursing literature were also examined to gain a broader understanding of workplace bullying. Findings: Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 29 publications
(250 reference statements)
8
150
1
14
Order By: Relevance
“…Nursing staff and management need to be educated about bullying what bullying behaviors look like and how to deal with bullying. By raising awareness about the issue, healthcare staff may become less tolerant of this negative behavior [27,32] .…”
Section: Resultsmentioning
confidence: 99%
“…Nursing staff and management need to be educated about bullying what bullying behaviors look like and how to deal with bullying. By raising awareness about the issue, healthcare staff may become less tolerant of this negative behavior [27,32] .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the nursing literature has mainly analyzed harassment and bullying from the point of view of the victim [25]. While many studies have dealt with the aforementioned aspect, research with the aim of understanding the reasons why nurses perform these behaviors is lacking.…”
Section: Cwb Has Been Categorized Into Actions Directed Toward Organimentioning
confidence: 99%
“…Research has shown that work situation of the victims may become so difficult that they finally either choose to leave work, or they are forced out of the workplace by means of dismissal or redundancy [14]. Health care workers seem to be more at risk of workplace bullying as compared to other occupations, yet majority of the data so far come from the studies of nurses [15,16]. Some studies investigating bullying arising from patients, colleagues and supervisors among medical doctors during training, residents, emergency physicians, ambulance personnel [17], young doctors and specialists with long career experience exist; including studies conducted in the United States [18][19][20][21], in some European countries [22][23][24][25] as well as in Japan [26].…”
Section: Introductionmentioning
confidence: 99%